R Representasi Maskulinitas Pada Tokoh Dola dalam Anime Laputa: Castle in the Sky (1986) - Kadek Dian Dewi; Kadek Eva Krishna Adnyani; Yeni Yeni (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2024)
This research aims to describe the representation of masculinity in the Dola character in the anime